Expanding the genetic landscape of Usher syndrome type IV caused by pathogenic ARSG variants - Bauwens, Miriam; De Man, Vincent; Audo, Isabelle; Balikova, Irina; Zein, Wadih M.; Smirnov, Vasily; Held, Sebastian; Vermeer, Sascha; Loos, Elke; Jacob, Julie; Casteels, Ingele; Désir, Julie; et al. (Clinical genetics, 2025)
Usher syndrome (USH) is the most common cause of deafblindness. USH is autosomal recessively inherited and characterized by rod‐cone dystrophy or retinitis pigmentosa (RP), often accompanied by sensorineural hearing loss. Variants in >15 genes have been identified as causative for clinically and genetically distinct subtypes. Among the ultra‐rare and recently discovered genes is ARSG, coding for the lysosomal sulfatase Arylsulfatase G. This subtype was assigned as “USH IV” with a late onset of RP and usually late‐onset progressive SNHL without vestibular involvement. Here, we describe nine new subjects and the clinical description of four cases with the USH IV phenotype bearing seven novel and two known pathogenic variants. Functional experiments indicated the complete loss of sulfatase enzymatic activity upon ectopic expression of mutated ARSG cDNA. Interestingly, we identified a homozygous missense variant, p.(Arg99His), previously described in dogs with neuronal ceroid lipofuscinosis. Our study expands the genetic landscape of ARSG‐USH IV and the number of known subjects by more than 30%. These findings highlight that USH IV likely has been underdiagnosed and emphasize the need to test molecularly unresolved subjects with deafblindness syndrome. Finally, testing of ARSG should be considered for the genetic work‐up of apparent isolated inherited retinal diseases. Mutations in ARSG are a very rare cause of Usher disease, assigned as “Usher type IV.” We identified 13 new subjects with mutations in ARSG, provide a clinical description of the subjects, and characterized the newly identified variants.